Development of intelligent home security system - Islam, Sayedul; Hossain, Zakir; Dutta, Sourav; Hossain, Shafiul (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.